Simultaneous Determination of Eosin-Yellow and Ponceau-S Using H-Point Standard Addition Method in Micellar Media. Issue 1 (2012) - Kaur, Amandeep; Gupta, Usha
Abstract : H -point standard addition method (HPSAM) is developed for simultaneous determination of eosin- Y and ponceau-s in micellar media. Nickel chloride (NiCl2 ) is used as chromogenic reagent for complexes formation of eosin- Y and ponceau- S food colorants. The measurements were carried out using sodium lauryl sulphate as a surfactant, in buffered solution at pH 6.0. The concentration range of 0.115-2.53 μg/mL of eosin- Y and 0.159-3.80 μg/mL of ponceau- S . The proposed procedures have been applied successfully for the simultaneous determination of eosin- Y and ponceau- S in synthetic binary mixtures and real samples.